(untitled) (UNED Research Journal, 2020)
In recent years the coyote (Canis latrans) has expanded its range in the tropical areas of Mexico and Central America. We report the first record of a coyote in the Calakmul Biosphere Reserve in the southeastern, Mexico. Using photo trapping, from December 2018 to June 2019, tree photographs of coyotes were obtained from a site located in the center of the southern core area of the reserve.